Fauna and flora of Gunung Datuk Recreational Forest, Negeri Sembilan, Malaysia: a brief documentation - Garba Jega, Bilyaminu; Charles Rejaram, Micheal; Mustaf, Muskhazli; Wan Solahudin, Wan Mohd Syazwan; Nulit, Rosimah; Abu Bakar, Noraini; Salihu Abba, Hammanjoda; Kong Yap, Chee (MedCrave Group, 2024)
The biodiversity of forests in Negeri Sembilan, such as the Gunung Datuk Recreational Forest, is remarkably diverse and supports a wide array of fauna and flora species. These species play crucial roles in nutrient cycling, pollination, medicinal and providing habitats for other species. The study documented nine (9) plant species of the Kingdom Plantae and family Ebenacae, Dioscoreaceae, Dipterocarpaceae, Arecaceae, Rubiaceae, Polypodiaceae, Piperaceae and Poaceae, four (4) fungal species of the kingdom Fungi and family Physalacriaceae, Podoscyphaceae, Omphalotaceae and Amanitaceae and five (5) animal species from the kingdom Animalia and family Trigoniulidae, Zephroniidae, Scincidae, Arebidae and Formicidae. The species abundance in the forest emphasizes the interconnectedness of biodiversity and its role in maintaining the ecological balance. This study integrates ecology, environmental science, and cultural values, providing a holistic framework for managing biodiversity. Preserving the forest biodiversity of Gunung Datuk is crucial for ecological stewardship, safeguarding cultural heritage, and ensuring sustainable development for future generations. This fosters a harmonious coexistence where biodiversity and human needs are harmonized.